MANUSIA DALAM AL-QURâAN (STUDI ATAS KITAB MAQÃL FÃ AL-INSÃN: DIRÃSAH QURâANIYYAH KARYA âÃâISYAH âABD AL-RAHMAN BINT AL-SYATHIâ) - Jannah, Miftahul (Jurnal Ilmiah Ilmu Ushuluddin, 2017)
This article examines about the exposure of human in the Qurâan according to âÃâisyah âAbd al-Rahman Bint al-Syathiâ. The object of this examination is her book of MaqÃ¢l fÃ® al-InsÃ¢n, and explained with thematic method. Actually, the book focused on human things. The author wants to apply one strict specific method to investigate how al-Qurâan uses several terms that refer to âhumanâ word, such as al-Basyar, al-InsÃ¢n dan al-Ins. Here, Bint al-Syathiâ tried to distinguish the meanings of those terms, which are often considered synonims, even almost all of dictionaries or books of exegesis in the classical tradition confirm these synonyms. However, she rejected the concept because the original Arabic tradition also rejected it. In her opinion, the Qurâan itself provided a very real representation and distinguished between the three conceptions.